Family Support for Patients Undergoing Chemotherapy Breast Cancer in the Chemotherapy Room Santa Elisabeth Hospital Medan Year 2023 - Rusmauli Marbun; Mestiana Br Karo; Gita Saniya Tumanggor (Jurnal Kesehatan LLDikti Wilayah 1 (JUKES), 2023)
Breast cancer is the second leading cause of death after lung cancer and is the main cause of cancer death in women. In treating breast cancer patients undergoing chemotherapy, family support is very necessary and important concern for breast cancer patients undergoing chemotherapy through family support so that sufferers have hope and a purpose in life. The aim of this study was to determine family support for patients undergoing breast cancer chemotherapy in the chemotherapy room at Santa Elisabeth Hospital, Medan. This research uses a qualitative method where data collection is carried out by interviews with 5 questions. The sampling technique is uses purposive sampling, namely by reducing respondents from the total population used with a total of 5 participants. Inclusion criteria are the general characteristics of research subjects from population that can be accessed and will be researched (Nursalam 2020). The inclusion criteria in were: patients aged over 30 years and patients who had undergone chemotherapy more than once. The data analysis technique used is thematic analysis with research results: family support is encouragement given by the family to breast cancer chemotherapy patients, support that can be given to breast cancer chemotherapy patients is in the form of praise from the family, family support can be seen from behavior that takes over the work of chemotherapy patients breast cancer, Family support provides open or non-confidential information to breast cancer chemotherapy patients. Family support can be provided by the presence of the family for breast cancer chemotherapy patien